2022
DOI: 10.4103/atm.atm_82_21
|View full text |Cite
|
Sign up to set email alerts
|

Long-term COVID-19 effects on pulmonary function, exercise capacity, and health status

Abstract: BACKGROUND: The long-term effects of respiratory function and related physiological characteristics of coronavirus disease 2019 (COVID-19) survivors have not yet been studied in depth. OBJECTIVE: To examine pulmonary function, exercise capacity, and health-related quality of life among COVID-19 survivors. METHODS: Eighty-five survivors with confirmed COVID-19 were evaluated at the end of 3 and 6 months after disease onset. The assessment incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
1
39
0
2
Order By: Relevance
“…It is unquestionable that patients with ARDS are at risk of sustaining long-term impairments. Previous studies have described impaired quality of life and pulmonary functions in patients with acute lung injury [5,12,[23][24][25][28][29][30][31][32][33] after ICU discharge.…”
Section: Discussionmentioning
confidence: 99%
“…It is unquestionable that patients with ARDS are at risk of sustaining long-term impairments. Previous studies have described impaired quality of life and pulmonary functions in patients with acute lung injury [5,12,[23][24][25][28][29][30][31][32][33] after ICU discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Wasting and stunting in malnourished children has also been associated with increased child mortality due to infectious diseases, such as pneumonia [ 15 ]. Bearing in mind COVID-19's long-lasting detrimental effects on overall health, especially lung function [ 16 ]and pneumonia as a complication of measles being an independent statistically significant risk factor for death [ 17 ], this situation gives a much bleaker outlook to the current measles outbreak with millions of children at risk of life-threatening complications. Unsurprisingly, case fatality rates have risen to 8–13%, as estimated by WHO [ 2 ].…”
Section: Challenges and Implicationsmentioning
confidence: 99%
“…Along with digestive manifestations, hepatic disorders, including liver damage, has been reported during the SARS-CoV-2 pandemic, with increased levels of aspartate amino-transferases and alanine amino-transferases [ 99 ]. A group of scientists observed biopsy reports of COVID-19-infected patients and revealed the pathological features of hepatic injuries, including portal inflammation, mild lobular inflammation and moderate microvascular stenosis [ 100 ]. Furthermore, pancreatic disorders that have been observed to be caused by SARS-CoV-2 in the human body include increased levels of amylase and lipase along with acute pancreatitis [ 92 , 101 ].…”
Section: Gastro-intestinal Manifestationsmentioning
confidence: 99%
“…It has been observed that patients suffering from SARS-CoV-2 experienced long-term health effects, including widespread fatigue, psychological distress, chronic pain and disturbed sleep, which leads to failure to return productive work for at least one year after the acute trauma of pandemic [ 100 , 113 ]. Wu et al (2005) first noticed that 10–18% of SARS-CoV-1-recovered patients exhibited symptoms related to depression, anxiety and post-traumatic stress disorders with elevated risk of severe symptoms of virus that have low emotional support and high-perceived life threats.…”
Section: Psycho-social Manifestationsmentioning
confidence: 99%